Thermal Impacts of Air Cavities Associated with Insulated Panels Deployed for Exterior Building Envelope Assemblies - Utsav Dahal; Moncef Krarti (Energies)
This paper presents a comprehensive investigation to evaluate the impacts of air cavities between existing walls and insulated panels on the overall R-values of the retrofitted building envelope systems, addressing a key challenge in exterior envelope retrofitting. The effects of several factors are considered including the air cavity thickness (ranging from 0.1 cm to 5 cm), airflow velocity (varying between 0.1 m/s and 1 m/s), and surface emissivity (set between 0.1 and 0.9), in addition to the thickness of the insulated panels (ranging from 1 cm to 7 cm). It is found that any increase in the air cavity thickness increases the overall R-values of the building envelope assemblies when air is trapped within the sealed cavity. However, when air convection is prevalent, the overall R-value of the retrofitted walls decreases with any increase in air velocity and air cavity thickness. For sealed air cavities, the analysis results show a 9% improvement in R-value of the retrofitted walls. However, the R-value of retrofitted walls with unsealed air cavities can degrade by 76% and 81% for natural and forced air flows, respectively. Emissivity adjustment is found to be the most effective in improving the thermal performance of building envelopes with sealed air cavities, increasing the R-value of retrofitted walls by 13.6% when reduced from 0.9 to 0.1.